2006
DOI: 10.1111/j.1439-0531.2006.00672.x
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis‐independent Poor Morphology of Bovine Embryos Produced by Multiple Ovulation

Abstract: ContentsIn multiple ovulation and embryo transfer (MOET) programmes in cattle, a considerable number of morphologically poor-quality embryos continue to be produced; this is one of the limiting factors of the technique. Apoptosis has often been implicated in developmental arrest and fragmentation; these are regarded as poor traits of embryonic quality in mammalian pre-implantation embryos. In the present study, apoptosis was assessed in morphologically poor-quality embryos in comparison with good-quality embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Within IVF bovine embryos, the stress-related protein p66 shc is upregulated in early arrest, while p53 seems to not be involved in the same function [60][61][62]. In contrast, within embryos developed in the uterus, developmental arrest has been described as being both apoptosis-dependent [63] and apoptosis-independent [64]. It is conceivable that gene expression upstream BAX differs between parthenotes and embryos, particularly in the way they channel apoptotic stimuli through p66 shc and p53 [11,65,66].…”
Section: Discussionmentioning
confidence: 96%
“…Within IVF bovine embryos, the stress-related protein p66 shc is upregulated in early arrest, while p53 seems to not be involved in the same function [60][61][62]. In contrast, within embryos developed in the uterus, developmental arrest has been described as being both apoptosis-dependent [63] and apoptosis-independent [64]. It is conceivable that gene expression upstream BAX differs between parthenotes and embryos, particularly in the way they channel apoptotic stimuli through p66 shc and p53 [11,65,66].…”
Section: Discussionmentioning
confidence: 96%
“…Controversies between the association of apoptosis and embryo viability still exist (Haouzi and Hamamah, 2009), as shown by similar apoptotic indexes found by TUNEL between developmentally arrested in vivo bovine embryos, fragmented morulae and non-fragmented morulae (Ikeda et al, 2006). Similar results have been reported in the human species by TUNEL and Annexin V (Antczak and Van Blerkom, 1999).…”
Section: Assessment Of Embryo Quality Through Senescence and Apoptosimentioning
confidence: 59%
“…Hardy & Spanos (2002) mentioned that cytoplasmic fragmentation may be a non-invasive marker of apoptosis-type programmed cell death, especially of the inner cell mass (ICM). Also, Ikeda et al (2006) have suggested that embryonic fragmentation is due to cellular division asymmetry, more than to the apoptosis process. However, in humans, the relationship between fragmentation and apoptosis has been described as subjective (Hardy et al, 1999;Jurisicova et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, in humans, the relationship between fragmentation and apoptosis has been described as subjective (Hardy et al, 1999;Jurisicova et al, 2003). Also, Ikeda et al (2006) have suggested that embryonic fragmentation is due to cellular division asymmetry, more than to the apoptosis process. The index of apoptotic cells remained the same in the morula stage, whilst the fragmentation index was 50% higher; indicating that apoptosis and fragmentation may be independent processes (Van Soom et al, 2003).…”
Section: Discussionmentioning
confidence: 99%